Teacher preparation for linguistically diverse classrooms a resource for teacher educators - Lucas, Tamara (Routledge, 2011)
Teacher educators today need knowledge and practical ideas about how to prepare all pre-service and in-service teachers (not just bilingual or ESL specialists) to teach the growing number of students in K-12 classrooms in the United States who speak native languages other than English. This book is at the forefront in focusing exclusively on the preparation of mainstream classroom teachers for this population of students. Part I provides the conceptual and contextual framework for the book, including a comprehensive discussion of relevant demographic trends and an analysis of national and state policies. Part II presents examples of initiatives in different institutional and geographic settings, highlighting three essential elements of teacher preparation: curriculum content, program design, and program coherence. Meeting a pressing need among teacher educators left to figure out, largely by trial and error, how best to prepare non-specialist classroom teachers to work with ELLs, this book both contributes to the research base and provides practical information to help readers envision possibilities they can apply in their own settings.